The Revolution of Education Implementation Through Digital-Based Drawing Learning in Grade VII Students at SMP 2 Jati Kudus (Catharsis, 2022)
Learning arts and culture focused on fine arts is generally carried out by practicing using wet or dry paint media. Along with the development of technology, the media for creating 2D art has developed, as an example is the presence of digital images which use gadget. SMP 2 Jati Kudus implements a digital-based learning system, by utilizing gadgets owned by students in creating 2D arts. This is an interesting phenomenon because at the same time, some schools have adopted a policy of prohibiting students from using gadgets. The ban on its usage does not apply to SMP 2 Jati Kudus, inwhich the school permits the students use gadgets as a medium for learning. Through this phenomenon, researchers see an opportunity for revolution and innovation in education through digital-based drawing learning, where most teachers of arts and culture focus on fine arts, still stuck with conventional learning. There fore this research will focus on digital-based learning activities which are implemented in SMP 2 Jati Kudus, in which the involve students of grade VII. The primary data in this study were obtained from interviews, observations, and document studies, as well as the data obtained which were then analyzed using the Milles and Huberman data analysis techniques. The results of this study show that digital-based learning activities at SMP 2 Jati Kudus are the first step in preparing students to face learning in the future, with virtual-based learning.